Digital Storytelling in Developing Expressive Language Skills in Early Childhood: A Phenomenological Study - Danang Prastyo; Budi Purwoko; Rofik Jalal Rosyanafi; Desika Putri Mardiani; Ardhana Reswari (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2025)
Digital technology advancements have created innovative opportunities in early childhood education, particularly through digital storytelling. This research is motivated by challenges in developing expressive language skills in children in the digital era and the lack of comprehensive literature on the effectiveness of digital storytelling in Indonesian early childhood education contexts. This study aims to explore and analyze the phenomenon of using digital storytelling as a learning medium to develop expressive language skills in children aged 5-6 years. The research employed a qualitative method with a phenomenological approach, involving 15 children and 8 teachers at Darul Mustofa Burneh Kindergarten, Bangkalan, Madura. The results indicate that digital storytelling significantly improves children's ability to express ideas, retell stories with more complex structures, and develop new vocabulary. Thematic analysis identified four main themes: (1) Improved Quality and Complexity of Expressive Language, (2) Increased Active Participation and Duration of Children's Speaking, (3) Positive Impact on Introverted Children, and (4) Increased Social and Collaborative Learning. This study concludes that appropriate and curriculum-integrated use of digital storytelling can be an effective strategy in developing expressive language skills in early childhood. This research contributes to the developme nt of innovative technology-based learning models that align with the developmental characteristics of children in the digital era.